Evaluasi Penggunaan Lazy Glasses Terhadap Postur Tubuh dan Tingkat Ketidaknyamanan Tubuh dan Mata Saat Menggunakan Aplikasi Tiktok di Perangkat Smartphone pada Mahasiswa - Risky Haryanto; Anang Fachrudin Adi Utomo; Atiqa Nusaibah; Putri Pratiwi Widasari; Fauzan Romadlon; Henry Dwi Prihartanto (Jurnal Sosioteknologi, 2026)
Indonesia is among the countries with the largest number of TikTok users worldwide, with a difference of about 3.52 million users compared to the country ranked first. The widespread use of smartphones for social media activities may influence users’ body posture and visual comfort. This study examined the effect of using lazy glasses on body posture and eye discomfort while operating the TikTok application on a smartphone in sitting and lying positions. Ten university students (mean ± SD age = 23.4 ± 0.97 years) participated in the experiment. Four experimental conditions were evaluated: lying without lazy glasses (WOLZB), lying with lazy glasses (LZB), sitting without lazy glasses (WOLZD), and sitting with lazy glasses (LZD). Body segment angles and perceived discomfort were analyzed for each condition. The results showed that LZD tended to produce smaller neck angles, while WOLZD resulted in smaller angles in the left elbow. Higher discomfort in the head and neck regions was observed in WOLZD, whereas LZD tended to increase pressure around the eyes. Overall, lazy glasses may reduce physical discomfort in certain viewing positions but do not always produce the most neutral posture.